The synergy among stakeholders to develop Pisang Island as marine tourism: The case of underdeveloped area - Dian Kagungan; Devi Yulianti (Masyarakat, Kebudayaan dan Politik, 2019)
This research is motivated by the problems that arise from the implementation of the strategy of tourism development and a creative economy in Pisang Island of Pesisir Barat District, Lampung Province. The purpose of this research is to analyze the synergy between various parties in the development of marine tourism in Pisang Island. The research uses descriptive and qualitative approaches. The data collection techniques in use include interviews, documentation, and observation. Data analysis is carried out through data reduction, data display, and conclusion. The results showed that the strategy of marine tourism development in Pisang Island was not well implemented as a result of the lack of co-operation between government, society, and investors. The government was the pioneer of the construction of facilities, in both the main facilities and infrastructure, for potential investors who would invest their capital. As a result of this research, the recommendations to be made are that local governments should increase extension activities (such as training and community education) to create community awareness. Furthermore, private sectors could invest their capital by pioneering the development of facilities that do not yet exist needed near tourism attractions.